CITRA DARI AKAR RUMPUT: Peran Masyarakat Kampung Heritage Peneleh Dalam Pembangunan Citra Publik Melalui Walking Tour - Dea Clarissa Raestya Novari (Halu Oleo University, 2025)
City branding in Indonesia is largely dominated by a top-down and symbolic approach, which often fails to reflect the authentic character and identity of local communities. This condition creates a gap between promotional messages and the lived social reality at the grassroots level. This study employs a qualitative approach with a case study design to analyse the role of community narratives in shaping the public image through walking tour activities. The research involved ten tourists and key members of the local tourism awareness group (Pokdarwis) who directly participated in cultural interpretation. Data were collected through in-depth interviews, participatory observations, and documentation, and were analysed using thematic-narrative content analysis combined with three-dimensional image analysis (cognitive, affective, and conative). The findings reveal that community narratives combining official history and local stories effectively construct a holistic and emotional perception of the city’s image. Tourists gained new knowledge, developed emotional connections with residents, and expressed intentions to revisit and share their experiences. In conclusion, sustainable public image formation depends not merely on formal promotional strategies but on authentic narratives emerging from the community. This study implies the importance of community engagement in urban communication strategies and highlights storytelling-based interpretation as a foundation for sustainable city branding.